MAKE IN INDIA - THE MANUFACTURING CONUNDRUM - Misra, Satya Narayan; Ghadai, Sanjaya Ku (PEOPLE: International Journal of Social Sciences, 2016)
The high octane propaganda of Make-in-India seeks to make India a global manufacturing hub, by taking advantage of its demographic dividend, democratic framework, and huge untapped demand. The paper traces the impact of dismantling License Permit Quota (LPQ) regime on growth and employment and criticality of ICOR and Ease of Doing Business to realize our full growth potential. It brings out the need to harness economy of scale by setting up a chain of economic zones on the coastline and ancillary them with the SMEs. Given the tepid FDI inflow, particularly into the power sector, the paper makes a strong case for exploring viable joint ventures so as not to allow India to become fishing zone for MNCs. Underlining the pivotal importance of social capital, the paper strongly calls for Centre-State synergy and identifies investment in IT hardware as a priority sector in this major policy footprint of India.